2023
DOI: 10.1111/psyp.14421
|View full text |Cite
|
Sign up to set email alerts
|

Fear lies in the eyes of the beholder—Robust evidence for reduced gaze dispersion upon avoidable threat

Alma‐Sophia Merscher,
Matthias Gamer

Abstract: A rapid detection and processing of relevant information in our environment is crucial for survival. The human eyes are drawn to social or threatening stimuli as they may carry essential information on how to behave appropriately in a given context. Recent studies further showed a centralization of gaze that reminded of freezing behaviors in rodents. Probably constituting a component of an adaptive defense mode, centralized eye movements predicted the speed of motor actions. Here we conducted two experiments t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 89 publications
(133 reference statements)
3
8
2
Order By: Relevance
“…Beyond Pavlovian biases in responses and RTs, we also found cue valence to affect gaze position: During the cue presentation, participants’ gaze showed less dispersion from the center of the screen for Avoid cues compared to Win cues in a time range around 200–280 ms after cue onset, with differences becoming stronger with learning. It is notable that, compared to previous studies reporting freezing of gaze (Merscher & Gamer, 2024; Merscher et al, 2022; Rösler & Gamer, 2019), the reduction of gaze dispersion observed in this study was temporally and spatially very constrained. This difference likely arises from differences in the experimental set-up.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Beyond Pavlovian biases in responses and RTs, we also found cue valence to affect gaze position: During the cue presentation, participants’ gaze showed less dispersion from the center of the screen for Avoid cues compared to Win cues in a time range around 200–280 ms after cue onset, with differences becoming stronger with learning. It is notable that, compared to previous studies reporting freezing of gaze (Merscher & Gamer, 2024; Merscher et al, 2022; Rösler & Gamer, 2019), the reduction of gaze dispersion observed in this study was temporally and spatially very constrained. This difference likely arises from differences in the experimental set-up.…”
Section: Discussioncontrasting
confidence: 90%
“…Beyond Pavlovian biases in responses and RTs, we also found cue valence to affect gaze position: During the cue presentation, participants’ gaze showed less dispersion from the center of the screen for Avoid cues compared to Win cues in a time range around 200–280 ms after cue onset, with differences becoming stronger with learning. This finding is reminiscent of previous findings of “freezing of gaze” induced by a threat of shock manipulation (Merscher & Gamer, 2024; Merscher et al, 2022; Rösler & Gamer, 2019). Note however that our paradigms extends these findings: Previous studies encouraged participants to visually explore photos of natural scenes while they prepared for a button press in order to prevent an electric shock.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This rather restricted laboratory setting is also reflected in the currently used stimulus material that was defined by a homogeneous distribution of pictorial features to prevent other notorious gaze dynamics to interfere (Merscher et al, 2022;Rösler & Gamer, 2019). A recent study indeed followed up on this limitation and showed that reductions of gaze dispersion robustly persisted even when more complex scenes were explored (i.e., social and threatening scenes; Merscher & Gamer, 2023). However, an important question for future studies whether and how the observed gaze effects would manifest in more dynamic settings and 3-dimensional environments.…”
Section: Discussionmentioning
confidence: 99%
“…Given that organisms can also actively cope with threats, passive confrontations however might not be sufficient to fully characterize the repertoire of defensive responses. Accordingly, several studies have demonstrated significant differences in autonomic responses to inevitable compared to avoidable threats (Merscher & Gamer, 2023;Merscher, Tovote, Pauli, & Gamer, 2022;Rösler & Gamer, 2019). In addition, these latter studies have identified a centralization of gaze during the anticipation of avoidable threats.…”
Section: Introductionmentioning
confidence: 99%